Why Do Some Motorbike Riders Wear a Helmet and Others Don't? Evidence from Delhi, India - Michael Grimm; Carole Treibich (Institute for the Study of Labor (IZA), 2014)
We focus on helmet use behavior among motorbike users in Delhi. We use a detailed data set collected for the purpose of the study. To guide our empirical analysis, we rely on a simple model in which drivers decide on self-protection and self-insurance. The empirical findings suggest that risk averse drivers are more likely to wear a helmet, there is no systematic effect on speed. Helmet use also increases with education. Drivers who show a higher awareness of road risks are both more likely to wear a helmet and to speed less. Controlling for risk awareness, we observe that drivers tend to compensate between speed and helmet use. The results can provide a basis for awareness-raising policies. Improvements to the road infrastructure bear the risk of leading to risk-compensating behavior.
Keywords: D10; I10; I15; K42; R41; 330; road safety; helmet use; risky health behavior; self-protection; self-insurance; India; risk-taking behavior